Analisis Penggunaan Software Matematika Geogebra dalam Meningkatkan Pemahaman Konsep Matematika: Systematic Literature Review - Laylani Harahap, Syafrida; Yahfizham (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
systematic literature review approach was the research strategy used in this study. The data used in this research were collected from scientific publications about mathematics learning software in 12 journals. After these data were examined, scientific articles that had been indexed by Google Scholar became the population used in this research. Using the Publish or Perish tool, a search was carried out to find material about Geogebra software and mathematics learning. Geogebra is a powerful tool for visualization and mathematical exploration, allowing students to manipulate geometric, algebraic, and statistical objects interactively. Research findings show that students’ math skills improve when they utilize Geogebra.